If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(5t + -4) + 5t = 7t + -7 Reorder the terms: -3(-4 + 5t) + 5t = 7t + -7 (-4 * -3 + 5t * -3) + 5t = 7t + -7 (12 + -15t) + 5t = 7t + -7 Combine like terms: -15t + 5t = -10t 12 + -10t = 7t + -7 Reorder the terms: 12 + -10t = -7 + 7t Solving 12 + -10t = -7 + 7t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-7t' to each side of the equation. 12 + -10t + -7t = -7 + 7t + -7t Combine like terms: -10t + -7t = -17t 12 + -17t = -7 + 7t + -7t Combine like terms: 7t + -7t = 0 12 + -17t = -7 + 0 12 + -17t = -7 Add '-12' to each side of the equation. 12 + -12 + -17t = -7 + -12 Combine like terms: 12 + -12 = 0 0 + -17t = -7 + -12 -17t = -7 + -12 Combine like terms: -7 + -12 = -19 -17t = -19 Divide each side by '-17'. t = 1.117647059 Simplifying t = 1.117647059
| 2w+4-(3w+6)= | | -75=3g | | 20=-5/3z | | 3p*1/3=114 | | (u-10)*6=48 | | 3*1/3p=114 | | x*log(x)=600000000 | | -2.4n-3+(7.8n+2)= | | Y=-1/2x-12 | | -.5(8x-6)=6x-7 | | 10+6+3x=7*3.5 | | -2m(1+4m)5=-13 | | 2(2l-3+l)=36 | | -(3/x)=0 | | 13/6-1/2 | | 10+4+3x=7*3.5 | | 24.5=2.5-4c | | 7+7y=12x-56 | | -(3/x)0 | | 7v^2+224=-84v | | 10x+20y=360 | | a(n-5)+6=bn | | 6q+1+(q+11)= | | 16+3x=7*3.5 | | 30-45=18 | | 1.25m*7=43.25 | | 2x^2dy=(3xy-y^2)dx | | X+1.5x+0.5x=75 | | sqrt(3x^2+4)-2x=0 | | 4-15=-7 | | -4+3x=20x+9 | | X+1.5x+0.5x= |